G472 Delayed diagnosis of a gluconeogenic disorder in children with hypoglycaemia and/or lactic acidosis: lessons learnt. (25th October 2020) - Sreekantam, S; Preece, MA; Gerrard, A; Hutchin, T; Shortland, G; Raiman, J; Vijay, S; Santra, S
Abstract : Aim: To describe the clinical course of children in whom the diagnosis of an underlying metabolic disorder was delayed due to a failure of obtaining urine for organic acid analysis at the time of initial presentation with hypoglycaemia and/or lactic acidosis. Method: Retrospective review of case notes of children who had a delay in diagnosis of Fructose 1, 6 bisphosphatase deficiency. Results: Five (4 male) children (age range 7 days – 6 yrs old) were identified. The majority (3/5) had presented with hypoglycaemia and lactic acidosis which responded to dextrose infusion. Two patients (twin siblings) presented with lactic acidosis only.Urine organic acids were measured at the initial presentation in only one patient.In 1/5 patients, urine was obtained at the time of hypoglycaemia but was stored for toxicology due to a lack of clarity on specimen request form regarding patient's clinical presentation.In 4/5 patients, subsequent urine analysis demonstrated glyceroluria and white cell enzyme analysis confirmed the diagnosis of Fructose 1, 6 bisphosphatase deficiency in all. Lack of appropriate screening resulted in 4/5 patients presenting with repeated episodes of decompensation with an average of 3.4 episodes per patient. In these patients, average time period between initial presentation and diagnosis with Fructose 1, 6 bisphosphatase deficiency was 13.25 months. Conclusion: Our case series emphasise the importance of obtaining urine for organic acid analysis at the time of hypoglycaemia and/or lactic acidosis to avoid delay in diagnosis and initiation of appropriate therapy. Timely diagnosis and treatment can prevent morbidity and potential mortality associated with repeated episodes of decompensation.Fructose 1, 6 bisphosphatase deficiency is a treatable metabolic disorder that can be identified with prominent glyceroluria during an acute episode; which might not be seen after recovery from illness. It is important to be aware of false positive results due to contamination from nappy creams and to ensure repeat organic acid analysis in these situations.Management involves avoidance of prolonged fasting and emergency regimen during illnesses which includes administration of glucose polymer and avoiding drinks with higher fructose content.